The role and status of women in the Soviet Union. Ed. by D.R. Brown. [With contribs of M.G. Field, P. Carden, V.S. Dunham a.o. With introd. by H.L. Roberts] (Teachers College Press, 1968)
With bibliogr., graph. and tabs.